AI in Criminal Justice: Balancing Efficiency with Ethical Concerns (Journal of responsible AI & ethics, 2026)
The integration of Artificial Intelligence (AI) into the criminal justice system has the potential to dramatically improve efficiency, reduce human error, and provide data-driven insights. However, the use of AI in decision-making processes, such as predictive policing, sentencing, and parole decisions, raises significant ethical concerns regarding fairness, transparency, and accountability. This paper explores the dual-edged nature of AI in criminal justice, examining the balance between the efficiency gains offered by AI and the ethical issues it presents. The study delves into the role of bias, discrimination, and the lack of transparency inherent in some AI models and their implications for the criminal justice system. By reviewing existing literature, case studies, and real-world applications, the paper provides a comprehensive overview of the current state of AI in criminal justice, its benefits, challenges, and ethical risks. Recommendations for improving the integration of AI in criminal justice are also discussed, emphasizing the need for transparent, accountable, and ethically grounded systems.